The role of religion, religiousness and religious participation in the school-to-work transition in Germany. - Roth, Tobias (Journal of Ethnic & Migration Studies, 2020)
It is a well-established finding that in Europe migrants are less successful in the labour market than natives. This is especially true for migrants stemming from predominantly Muslim countries. Against this background, there is a strong interest in the role religion and religiosity plays for the structural integration of migrants. We add to this research by investigating the role of religious affiliation, private religiousness and public religious participation in the school-to-work transition of adolescents in Germany. Due to social and political relevance, our main focus lies on differences between Muslims and Non-Muslims. Our results indicate that substantial barriers exist in the school-to-work transition for Muslim adolescents who were born, raised and educated in Germany. The Muslim gap is clearly more pronounced for adolescents who are active in a religious community than for those who are not. In contrast, being religious and praying frequently is not decisive for the Muslim gap.